Overview of Some Gaps Regarding the Regulation of Construction Insurance in Ethiopia: A Note - Messelu, Mamenie Endale (Bahir Dar University Journal of Law, 2023)
Construction is a risky business. However, such risk can be managed, minimized, shared, or transferred trough insurance. In the developed world, it is difficult to practice construction business in the absence of sufficient cover of insurance. Adequate insurance policy could satisfy the interest of the general public, client, construction workers, and other concerned parties. In Ethiopia, though construction insurance is evolving, it is not given proper attention by concerned stakeholders such as law makers and legal professionals. Accordingly, this note explores the legal lacunas observed in the regulation of different types of insurance policies that are apt to manage risks on construction projects in Ethiopia. To discover the gaps and scrutinize the contesting legal issues, the writer employed a doctrinal research method. In the investigation, it is found out that variables such as rigid standard insurance policies, complex insurance policy language, absence of mandatory insurance for license renewal — mainly for contractors and consultants, excessively expensive premium, and lack of coordination between parties of the insurance policies are major sources of legal gap in this regime of law. As a result, the writer suggests areas of improvement to rectify these gaps. Particularly, it is imperative for the legislature synchronize the insurance policy laws in the country, eliminating conflicts, make insurance mandatory for license renewal, set fair insurance policy premium, and use concise language in drafting the policies.